Hydrogels: One Step Creation of Multifunctional 3D Architectured Hydrogels Inducing Bone Regeneration (Adv. Mater. 10/2015). (March 2015) - Neffe, Axel T.; Pierce, Benjamin F.; Tronci, Giuseppe; Ma, Nan; Pittermann, Erik; Gebauer, Tim; Frank, Oliver; Schossig, Michael; Xu, Xun; Willie, Bettina M.; Forner, Michèle; Ellinghaus, Agnes; et al.
<x xml:space="preserve">Abstract</x> The back cover highlights the unique degradation behavior of hydrogels with 3D architectures (ArcGels). Hydrolytic cleavage of bonds results in a merging of pores, comparable to soap bubbles. This mechanism, described by A. Lendlein and co‐workers on page 1738, results in pore growth during degradation, which putatively leads to mechanical stimulation of cells during the in vivo regeneration of bone. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>